PROBLEMATIKA HUKUM PENGELOLAAN SAMPAH DI KOTA PEKANBARU - Oktapani, Silm; Ardiansah, Ardiansah (Universitas Ekasakti, 2021)
The existence of garbage is a very serious matter in Pekanbaru City, with the increasing population resulting in an increase in the amount of waste produced every day. It is a concern for the Pekanbaru City Government to be able to overcome the problems that are increasing day by day. Regional Regulation Number 8 of 2014 concerning waste management is the basis for the implementation of the waste management policy. This study aims to see what are the legal problems for waste management in Pekanbaru City. The sociological law method is a method in this research to see how the law enforcement process is and how the law is enforced in society. The difficulty of changing people's habits in sorting organic and inorganic waste has made the waste management process unable to run optimally, and the lack of waste transport fleets is also one of the problems in waste management. The importance of the optimal role of the Pekanbaru City Government to the waste bank as an organization that helps the Pekanbaru City Government in its efforts to save money.